The Evolution of Public-Private Partnerships in a Comparison between Europe and Italy: Some Perspectives for the Energy Sector - Rossi, Matteo; Festa, Giuseppe; Gunardi, Ardi (International Journal of Energy Economics and Policy, 2019)
The recent global economic and financial crisis has generated new challenges for all public governments. In a number of countries, anti-crisis packages included innovative public actions, realized also in combination with private investments, like in the case of Public-Private Partnership (PPP), which combines the resource of government agents with those of private agents in order to realize public-interest aims. In this study, we have conducted a general analysis on PPP models, in order to present some evidences from a comparison between EU-28 (European Union with 28 countries) and Italy in the 2008-2016 period, with specific considerations on the energy sector. The various trends demonstrate a substantial evolution about global numbers and values of the Public-Private Partnership initiatives in EU-28 and Italy, and underline several constraints and challenges for successful PPP projects, even specifically for the energy sector. Keywords: Public-Private Partnership, EU-28 Italy comparison, energy. JEL Classifications: G38, M21, Q48 DOI: https://doi.org/10.32479/ijeep.7815